Perlindungan Hukum bagi Debitor di Indonesia Sehubungan Tidak Adanya Insolvency Test - Aprita, Serlika (UIN Jakarta, 2021)
The embodiment of legal protection for debtors whose companies still have the prospect of continuing but the debtor's financial condition in a state of inability to pay must be declared bankrupt due to the absence of an insolvency test which is considered contrary to the application of the going concern principle, which is related to the existence of expectations regarding the concept of the Indonesian Bankruptcy Law. in the future, especially regarding the shift in the purpose of the Bankruptcy Law, where initially the Bankruptcy Law aimed to liquidate debtor's assets, so it is hoped that in the future the Bankruptcy Law will in its development change as a means of reorganizing debtors in continuing their business activities, where this goal is not embodied in Law Number 37 of 2004 concerning Bankruptcy and PKPU.